Current practices for paediatric procedural sedation and analgesia in emergency departments: results of a nationwide survey in Korea. Issue 3 (19th April 2012) - Seo, Jun Seok; Kim, Do Kyun; Kang, Youngjoon; Kyong, Yeon Young; Kim, Jin Joo; Ahn, Ji Yun; Lee, Ji Sook; Jang, Hye Young; Jung, Jin Hee; Choi, Yoon Hee; Han, Seung Baik; Lee, Jin Hee
Abstract : Objective: Procedural sedation and analgesia (PSA) in children has become a standard tool in emergency settings, but no national PSA guidelines have been developed for the emergency department (ED) in Korea. Therefore, we investigated the practice of PSA and the level of adherence to institutional PSA guidelines in EDs of teaching hospitals. Methods: This study was a cross-sectional, web-based survey. The study subjects were the faculty of EDs from 96 teaching hospitals. The questionnaire was posted on an internet site, and the participants were requested that the questionnaire be answered by email and telephone in May 2009. Results: The questionnaires were completed by 67.7% of the participants. Only 20% of EDs had institutional PSA guidelines, 21.5% of those had discharge criteria and 13.8% of EDs had a discharge instruction form. Residents were administered PSA at 76.9% of EDs. The airway rescue equipment was near the area where PSA was performed in 76.9% of EDs. The most commonly used medication for both diagnostic imaging and painful procedure was oral chloral hydrate (87.7%, 61.5%). In 64.6% of EDs, patients were monitored. In only 21 cases, EDs (50.0%) monitored the patients to recovery after PSA or discharge. Conclusions: Current PSA for paediatric patients have not been appropriately applied in Korea. Unified PSA guidelines were rare in the hospitals surveyed, and many patients were not monitored over an appropriate duration, nor did they receive adequate medications for sedation by the best trained personnel. Therefore, the national PSA guidelines must be developed and implemented as early as possible.